More tales by Polish authors; - Benecke, Else C. M. (Else Cecilia Mendelssohn), 1873-1917, tr.; Prus, Bolesław, 1847-1912.; Sieroszewski, Wacław, 1858-1945.; Żeromski, Stefan, 1864-1925.; Reymont, Władysław Stanisław, 1867-1925.; Szymaṅski, Adam, 1852-1916.; Busch, Marie, joint tr. (New York, Longmans, Green & co., 1916)
Maciej the Mazur, by Szymaṅski.--Two prayers, by Szymaṅski.--The trial, by St. Reymont.--The stronger sex, by Zeromski.--The Chukchee, by Sieroszewski.--The returning wave, by Prus [pseud.] Mode of access: Internet.